Continuance Intention Mechanism of Middle School Student Users on Online Learning Platform Based on Qualitative Comparative Analysis Method. (20th March 2022) - Chen, Guomin; Chen, Pengrun; Huang, Wenxia; Zhai, Jie
Abstract : The research on the users' continuance intention behavior of online learning platforms is not a new topic. In the past, more studies were conducted on users of MOOC online learning platforms, which are based on symmetric causality. This study adopts the qualitative comparison analysis method to build configuration model by combining platforms, students, parents, teachers (4 level seven elements) with middle school students' continuance intention. The configuration analysis identifies the user' retention path of middle school students on online learning platform under the collaborative influence of multi-level elements, summarizes the online learning platform of continuance intention mechanism and implementation path for middle school students and reveals that the users of online learning platform for middle school students keep clear of the mechanism of action and realistic choice. In the end, the user retention mechanism of middle school students' online learning platform is summarized, including platform quality orientation, platform interaction orientation, and "parent-teacher" dual drive.